2007
DOI: 10.1128/jb.00770-07
|View full text |Cite
|
Sign up to set email alerts
|

MukEF Is Required for Stable Association of MukB with the Chromosome

Abstract: MukB is a bacterial SMC(structural maintenance of chromosome) protein required for correct folding of the Escherichia coli chromosome. MukB acts in complex with the two non-SMC proteins, MukE and MukF. The role of MukEF is unclear. MukEF disrupts MukB-DNA interactions in vitro. In vivo, however, MukEF stimulates MukB-induced DNA condensation and is required for the assembly of MukB clusters at the quarter positions of the cell length. We report here that MukEF is essential for stable association of MukB with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
49
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 38 publications
0
49
0
Order By: Relevance
“…In eukaryotes, Topo II and condensin SMC subunits are abundant components of histone-depleted mitotic chromosomes (69). Similarly, the MukBEF complex remains stably associated with the E. coli chromosome following cell lysis, suggesting that this complex also serves a scaffolding role that organizes the bacterial chromosome into a higher-order structure (71). Electron microscopy studies have revealed that MukBEF complexes can aggregate to form rosettes (72), and high-resolution structural studies suggest that this process may occur through MukF/E mediated bridging of MukB dimers (73).…”
Section: Discussionmentioning
confidence: 99%
“…In eukaryotes, Topo II and condensin SMC subunits are abundant components of histone-depleted mitotic chromosomes (69). Similarly, the MukBEF complex remains stably associated with the E. coli chromosome following cell lysis, suggesting that this complex also serves a scaffolding role that organizes the bacterial chromosome into a higher-order structure (71). Electron microscopy studies have revealed that MukBEF complexes can aggregate to form rosettes (72), and high-resolution structural studies suggest that this process may occur through MukF/E mediated bridging of MukB dimers (73).…”
Section: Discussionmentioning
confidence: 99%
“…How then to reconcile the biochemical observations to those in vivo that indicate mukE and mukF mutations have the same phenotype as mukB mutations (33,34), and that MukB ATPbinding and MukEF are required for MukB localization in the cell (11,12)? These observations are not necessarily contradictory.…”
Section: Topological Alteration Of the Dna Observed In The Reactions mentioning
confidence: 99%
“…MukB binds linear and circular DNA in vitro and can induce negative supercoils and knots in relaxed circular DNA in the presence of a topoisomerase (10). Binding of MukB to chromosomal DNA in vivo requires ATP and MukEF (11,12), although MukB DNA binding in vitro does not (10,13).…”
mentioning
confidence: 99%
“…B. subtilis SMC and its homolog, MukB, in E. coli are composed of two head regions at N and C termini, setting up an ATPase domain separated by two heptad-rich regions forming a single internal long coiled coil that are connected by a flexible hinge domain in the middle. Homodimerized SMC proteins linked by the hinge domain (17) form a complex with ScpA and ScpB (segregation and condensation proteins A and B) (23), while MukB interacts with MukF and MukE in E. coli correspondingly (27). The B. subtilis smc mutant shows a severe temperature-sensitive lethal phenotype with irregular chromosome organization and chromosome segregation defects (4,24).…”
mentioning
confidence: 99%